2002
DOI: 10.1016/s1097-2765(02)00588-9
|View full text |Cite
|
Sign up to set email alerts
|

The Assembly of Ebola Virus Nucleocapsid Requires Virion-Associated Proteins 35 and 24 and Posttranslational Modification of Nucleoprotein

Abstract: Ebola virus encodes seven viral structural and regulatory proteins that support its high rates of replication, but little is known about nucleocapsid assembly of this virus in infected cells. We report here that three viral proteins are necessary and sufficient for formation of Ebola virus particles and that intracellular posttranslational modification regulates this process. Expression of the nucleoprotein (NP) and virion-associated proteins VP35 and VP24 led to spontaneous assembly of nucleocapsids in transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
237
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(260 citation statements)
references
References 45 publications
21
237
1
1
Order By: Relevance
“…MARV NP forms large helical structures resembling the nucleocapsids found in mature virions [22,34]. For EBOV, the minimal protein requirements for the formation of nucleocapsid-like structures are NP, VP35 and VP24 [17,35]. Recently, Noda and colleagues have proposed a model for EBOV nucleocapsid formation and subsequent budding [23].…”
Section: Nucleocapsid Assemblymentioning
confidence: 99%
“…MARV NP forms large helical structures resembling the nucleocapsids found in mature virions [22,34]. For EBOV, the minimal protein requirements for the formation of nucleocapsid-like structures are NP, VP35 and VP24 [17,35]. Recently, Noda and colleagues have proposed a model for EBOV nucleocapsid formation and subsequent budding [23].…”
Section: Nucleocapsid Assemblymentioning
confidence: 99%
“…NP encapsidates the genome and protects it from nucleases. 17,18 VP30 is a transcription anti-terminator 19,20 and regulates the switch between transcription and replication. 21,22 VP35 acts as a cofactor of the polymerase, 23,24 and VP40 may also play a role in genome replication and transcription.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 VP35 acts as a cofactor of the polymerase, 23,24 and VP40 may also play a role in genome replication and transcription. 25 VP24 and VP35 participate in viral nucleocapsid assembly, 18 and VP40 is essential for virus budding and assembly. [26][27][28] In addition, GP, VP24, VP30, VP35 and VP40 interact with multiple host proteins to complete the viral life cycle and to suppress the host immune response.…”
Section: Introductionmentioning
confidence: 99%
“…It contains an axial channel of 10-15 nm in diameter surrounded by a high electron-dense layer of 20 nm in diameter [6]. Recently, conventional TEM demonstrated that three proteins, nucleoprotein (NP), putative minor matrix protein (VP24), and polymerase cofactor (VP35) were necessary and sufficient for the formation of nucleocapsid-like (NC-like) structures in a mammalian expression system [10].To obtain 3D structural information on these NC-like structures, we used ET to study NC-like structures present in the cytoplasm of cells expressing NP, VP24, and VP35.First, to confirm the formation of the NC-like structures, we transfected 10 6 human embryonic kidney (293T) cells with 2 µg of pCEZ-NP, 2 µg of pCEZ-VP24, and 2 µg of pCEZ-VP35, which express NP, VP24, and VP35, respectively [14]. At 72 hr post-transfection, 293T cells expressing these viral proteins were prefixed with 2.5% glutaraldehyde in 0.1 M cacodylate buffer (pH 7.4), and washed with the same buffer.…”
mentioning
confidence: 99%
“…It contains an axial channel of 10-15 nm in diameter surrounded by a high electron-dense layer of 20 nm in diameter [6]. Recently, conventional TEM demonstrated that three proteins, nucleoprotein (NP), putative minor matrix protein (VP24), and polymerase cofactor (VP35) were necessary and sufficient for the formation of nucleocapsid-like (NC-like) structures in a mammalian expression system [10].…”
mentioning
confidence: 99%